Synthesis of Aryl Carboxylic Acids through Ambient Electro-oxidation of Arylacetylenes - Yuan, Hongyan; Sun, Manxin; Zhang, Tong; Wu, Guohao; Zhang, Yanhua (Synthesis, 2023)
An efficient and environment-friendly synthesis of aryl carboxylic acids through the ambient electro-oxidation of the arylacetylenes is demonstrated. The reaction proceeds smoothly at certain applied potentials in a mixed solution of acetonitrile and water with potassium peroxymonosulfate (Oxone) as the additive. The isolated yields of the desired products are good up to 90%, and the reaction exhibits excellent functional-group tolerance. In this electrochemical system, transition metal catalysts, extra acids/bases, and high temperature are not required. This method may open up a pathway for the synthesis of carboxylic acids by the electrochemistry strategy.
Keywords: arylacetylenes; aryl carboxylic acids; electrochemistry; oxidation; organic synthesis